Impact of shading on PV systems - Lee, Kong Zhou (2015)
Global warming – often used interchangeably with climate change is and always will be a prevalent topic in the news and scientific research as it is a major concern to countries around the world today. Global warming is a phenomenon whereby solar radiation that has reflected back of the surface of the earth remains trapped at atmosphere levels due to the build up of carbon dioxide and other green house gasses rather than being emitted back into space. The effect of this is a warming of the global atmosphere. Every year almost 7 billion tons of carbon dioxide is released into the atmosphere by human activity. Global warming is in the earth’s upper atmosphere directly caused by human burning of fossil, fuels, industrial, farming and deforestation. It has become important that alternative sources of energy, which can reduce our carbon footprint, be utilized. Solar energy is a clean alternative source of renewable energy which has tremendous potential in Singapore. In this report, a study of Singapore’s local climate will be analyzed and discussed along with its methodologies and as such providing an insight into the intermittent nature of solar energy in our region. The first part of this report will discuss on the research the author has conducted to better understand the topic of photovoltaic and solar energy, irradiance. The next portion will include how the solar energy is calculated and how it is statistically analyzed using MATLAB. The final topic in this report will be on diversity which inevitably will be part of the future works for the continuation of this project and its conclusion.